Pengaruh Terpaan Informasi Line Today Terhadap Kepuasaan Informasi pada Mahasiswa Komunikasi Universitas Islam Riau - Negara, Satrio Mangku; Riauan, Muhd Ar. Imam (Riauan Consulting and Communication, 2022)
The aim of this study is how much the influence of Line Today's exposure to the satisfaction of fulfilling the information needs of the students of the communication science faculty of Riau Islamic University. The data analysis technique used in this study is quantitative with a simple linear regression method. The population was taken from the 2017 faculty of communication science students, 2016-2015 at Riau Islamic University, with a total of 763 students at the time of this study, and with a sample of 88 respondents. The independent variable is the exposure of the Line Today feature which consists of three sub-variables, namely frequency, duration, attention. The dependent variable is the satisfaction of fulfilling the information needs of communication science faculty students at Riau Islamic University. Data collection is done by distributing questionnaires to students of communication science faculties in Riau Islamic University. By using a simple linear regression method, the results of calculations on the satisfaction of fulfilling information needs after getting exposure to information, the respondent's answer about Line Today exposure with the average respondent's answer of 53% said agree. From the results of the t test, the value of t calculated for Line Today Expected variable is 8,204 greater than the table of 1,987, and PV value is 0,000 <0,05, the results of this study indicate that Line Today exposure has a significant effect on Satisfaction of Information Needs at Faculty of Science Students Communication.